Uncertainty of LiF thermoluminescence at low dose levels: Experimental results. (July 2022) - Sadek, A.M.; Abdou, N.Y.; Alazab, Huda A.
Abstract: The LiF:Mg, Ti (TLD-100) thermoluminescence (TL) detectors are widely used in many dosimetric applications, particularly in personal dosimetry area. In the present study, the uncertainty of TLD-100 measurements at the low dose levels has been assessed for different TL readout analysis methods. The criteria used to evaluate the minimum measurable dose (MMD) have been also investigated. It has been found that between-sample variations and the precision of the TL measurements were the significant uncertainty components. However, the precision of the measurement is critically dependent on the TL readout analysis and background (BG) subtraction methods. The estimation of the MMD based on the 3 σ B G approach may lead to inaccurate measurements. On the other hand, a new criterion for evaluating the MMD based on the signal-to-noise ratio and can be evaluated from the glow-curve deconvolution analysis has been established. It has been shown that the implementation of this criterion ensures acceptable levels for both the precision and trueness of TL measurements. Highlights: The uncertainty of LiF TL detector at low dose levels has been assessed. A new criterion for the minimum measurable dose (MMD) has been established. The 3 σ B G MMD criterion may not provide accurate measurements. The TL signal should be ≥ 10 times the BG to achieve an uncertainty level < 10 % .